A Comparative Study to Determine the Efficacy of Piracetam over Carbamazepine in the Treatment of Idiopathic Tinnitus - Ravishankar S. N., Vijayendra Simha. N, (International Journal of Innovative Research in Medical Science, 2017)
Tinnitus is a very common complaint faced by both medicine and ENT doctors alike which hampers the daily day to day activities of these patients. Many of them are idiopathic cases and there is still no complete cure with whatever advancement we have made in this field. In this study we try to determine whether Piracetam or Carbamazepine is efficient in treating such cases of idiopathic tinnitus.